# 7. Addition and Subtraction of Fractions

Recall that to **add** or **subtract** fractions, we
need to have the **same denominator.**

### Example 1

Add the fractions: `2/3+4/15`

**Solution: **Here, the **lowest common denominator** which we can use is
`15`. So we have:

`2/3+4/15=10/15+4/15=14/15`

**Subtraction** works in the same way, as we see in the next example.

### Example 2

`6/7-5/14`

Answer

Our **lowest common denominator** this time is 14. So we
have:

`6/7-5/14=12/14-5/14=7/14=1/2`

When we have algebraic expressions involving fractions, we need to use the same process.

### Example 3

`a/(6y)-(2b)/(3y^4)`

Answer

The lowest common denominator here will be
6*y*^{4}.

So we have:

`a/(6y)-(2b)/(3y^4)=(ay^3)/(6y^4)-(4b)/(6y^4)`

We can write this as:

`(ay^3-4b)/(6y^4`

### Example 4

`(x-1)/(2x^3-4x^2)+5/(x-2)`

Answer

We factor the first denominator to get an idea of what to do:

`(x-1)/(2x^3-4x^2)+5/(x-2)`

`=(x-1)/(2x^2(x-2))+5/(x-2`

We can see now that if we multiply the second fraction by
2*x*^{2}, we will have a common denominator:

`(x-1)/(2x^2(x-2))+(5xx2x^2)/(2x^2(x-2))`

`=(x-1+10x^2)/(2x^2(x-2)`

We would normally write this as:

`(10x^2+x-1)/(2x^2(x-2)`

### Exercises

Simplify the following.

**(1)**** **`2/(s^2)+3/s`

Answer

`2/(s^2)+3/s`

`=2/(s^2)+(3s)/(s^2)`

`=(2+3s)/(s^2)`

**(2)**** **`5+(1-x)/2-(3+x)/4`

Answer

The lowest common denominator is 4.

`5+(1-x)/2-(3+x)/4`

`=20/4+(2(1-x))/4-(3+x)/4`

`=(20+2-2x-3-x)/4`

`=(-3x+19)/4`

**(3)**** **`5/(6y+3)-a/(8y+4)`

Answer

`(5)/(6y+3)-(a)/(8y+4)` `=5/(3(2y+1))-a/(4(2y+1))`

`=20/(12(2y+1))-(3a)/(12(2y+1))`

`=(20-3a)/(12(2y+1))`

We have factored out the 3 at the bottom of the first fraction and the 4 at the bottom of the second fraction.

In the 3rd line, we find the lowest common denominator, 12(2*y* + 1), and multiply top and bottom of the two fractions accordingly.

The last line is a tidy up step.